Generation Z Consumers’ Perceptions of Purchasing Intention Toward Organic Agricultural Products in Padang City - M. Farrasky Delas Putra; Yozi Putri Sakinah; Sultani Sultani; Hermawan Hermawan; Riza Pebriani (Utan Kayu Publishing, 2025)
This study investigates Generation Z consumers’ purchase intention toward organic agricultural products in Padang City by examining the influence of digital, economic, social, and perceptual factors. The research topic is important due to the increasing global demand for organic food and the need to understand the behavioral determinants that shape healthy consumption patterns among young populations. The study hypothesizes that these four variables significantly affect purchase intention. A quantitative approach was employed using an online survey distributed to 73 Generation Z respondents, and data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that all variables significantly contribute to purchase intention, with consumer perception emerging as the strongest predictor, followed by digital and social factors, while economic constraints remain a major barrier. The model explains 62% of the variance in purchase intention, indicating substantial predictive power. These findings highlight that health-related beliefs, digital exposure, and social norms play a critical role in shaping healthy consumption behavior among young consumers. The study contributes to health sciences by demonstrating that promoting organic food consumption requires integrating health education with digital communication and socio-economic considerations